2009
DOI: 10.2174/1876823700901010023
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Concentration is Independently Associated with Variation in the LPL Gene in African American and European American Women

Abstract: Abstract:Objective: The regulation of triglyceride (TG) metabolism may be affected by many factors including: race/ethnicity, body composition, body fat distribution, insulin action, and the activity of the lipoprotein lipase (LPL) enzyme. This study was designed to identify the independent effects of body composition, body fat distribution, insulin action, and LPL genetic variation on TG and HDL-C concentration. Subjects: The study consisted of premenopausal European American (EA) (n=114) and African American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Triglycerides are transported from the liver to other tissues primarily by VLDL-C. By contrast, the liver does not produce LDL-C, which instead appears to emerge as a VLDL-C derivative after lipoprotein lipase partially eliminates triglycerides [51]. As proposed by Casazza et al [52], a reduction in the lipoprotein lipase activity, leading to reduced triglyceride assimilation from the circulatory system, might explain the noted rise in the levels of triglycerides. The present study found that, in the L-NAME group, the levels of Figure 4: Gene expression of angiotensin II receptors (AT1A, AT1B, and AT2) of treatment groups compared to nontreated control group (relative to GAPDH (RQ)), using the 2 -ΔΔCT method.…”
Section: Discussionmentioning
confidence: 99%
“…Triglycerides are transported from the liver to other tissues primarily by VLDL-C. By contrast, the liver does not produce LDL-C, which instead appears to emerge as a VLDL-C derivative after lipoprotein lipase partially eliminates triglycerides [51]. As proposed by Casazza et al [52], a reduction in the lipoprotein lipase activity, leading to reduced triglyceride assimilation from the circulatory system, might explain the noted rise in the levels of triglycerides. The present study found that, in the L-NAME group, the levels of Figure 4: Gene expression of angiotensin II receptors (AT1A, AT1B, and AT2) of treatment groups compared to nontreated control group (relative to GAPDH (RQ)), using the 2 -ΔΔCT method.…”
Section: Discussionmentioning
confidence: 99%
“…Large epidemiologic studies have demonstrated that subjects with hypertension have a marked increase in the prevalence of hypercholesterolemia (Yang et al, 2011). The observed increase in TGs might be due to a decrease in the activity of lipoprotein lipase, resulting in decreased uptake of TGs from the circulation (Casazza et al, 2009). Hypertension frequently coincides with elevated levels of triglycerides (TGs).…”
mentioning
confidence: 99%